Boats - Stickland, Paul (Milwaukee Gareth Stevens Publishing, 1998)
Illustrations and brief text present various types of boats: ferries, rowboats, sailing ships, oil tankers, and more.
Keywords: Boats and boating; Ships; On The Move series